“El pensamiento crítico para la lectura” - Mendaño Yanchapanta, Lidia Tarcila (2023)
Educational process presents changes that demand new competences to answer the present society needs which should be focused on the students’ critical skills development in order to train them as critical and reflexive beings as a part of their integral growing. Thus, teachers should apply new teaching strategies based on the critical thinking in the pedagogical process, so that they contribute the cognitive, procedural and attitudinal skills meaningfully. Teachers in their pedagogical process have focused the class in traditional practices for this reason they are considered as the unique knowledgment possessors. In addition, applied strategies do not contribute to critical thinking development, consequently students learning is rote, receptive and mechanical. The objective of this research is to strengthen reading through strategies based on critical thinking in the fifth year of General Basic Education, at the school "Agustín Albán" located in the province of Cotopaxi, canton Pujilí, parish La Matriz. The methodology was based on the interpretative approach since it allowed understanding the reality of the educational context in its own nature. The present work is based on qualitative research because the meanings of the research subjects were interpreted. Its methodological design is focused on analysis because the descriptive analysis was made to define categories through the reduction of information. The method applied is the inductive method that was carried out in the analysis and synthesis of the information collected, the technique is observation and was directed to the tutor teacher and thirty-five students. The results of the application of the practical class about critical thinking for reading show the tale as a teaching strategy that give us the opportunity to learn in a different way than the traditional one. Also, the tale is a teaching strategy that guides the development of learning because it generates interest, motivation and arouses curiosity for reading, which allows the student to develop reasoning skills in order to reflect and generate opinions in any life situation, further, the reading improves communication, vocabulary and analytical skills in different areas of knowledge. Therefore, this project contributes to reasoning development by means of new material, that shows the educational practice creativity, thus it motivates students to reading through reflection, comprehension, interpretation, and evaluation, these skills promote critical thinking development in their learning process.